Cogeneration of energy in solar systems - a study case, Kosovo - Bukurije Hoxha; Rexhep Selimaj; Drenusha Krasniqi; Sabrije Osmanaj (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Nowadays the main goal of sustainable energy supply is the use of renewable energy sources and, in addition, the increased efficiency of the energy used. One possibility of using renewable energies is the use of solar energy through photovoltaic panels. Taking into account the meteorological characteristics of the country in which the study takes place, it appears that the use of photovoltaic panels will be available most of the time during the year. We applied a model of hybrid solar collectors for maintaining the cell temperature near 25°C by introducing a flat plate cover integrated with solar cells. This method represents a way to increase the efficiency of the solar collector. This will enable the production of electricity from the part of the photovoltaic panel incorporated into the solar collector, in which the water temperature will increase, and this heat from the water is due to the effect of sunlight and as a result of cooling the part of the photovoltaic panel. This represents an increase in the efficiency of the system and the main purpose of our analysis.